2015
DOI: 10.1155/2016/9730467
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dopamine and Its Dysfunction as a Consequence of Oxidative Stress

Abstract: Dopamine is a neurotransmitter that is produced in the substantia nigra, ventral tegmental area, and hypothalamus of the brain. Dysfunction of the dopamine system has been implicated in different nervous system diseases. The level of dopamine transmission increases in response to any type of reward and by a large number of strongly additive drugs. The role of dopamine dysfunction as a consequence of oxidative stress is involved in health and disease. Introduce new potential targets for the development of thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
174
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(180 citation statements)
references
References 108 publications
3
174
0
3
Order By: Relevance
“…The dopamine theory of schizophrenia, based on hyperactive dopamine projections in the mesolimbic system and reduced dopamine projections in the mesocortical system (Juárez Olguín et al, 2016), is the prevalent explanation of schizophrenia symptoms now. Alterations in striatal D2 receptors cause positive symptoms, and impairments in the prefrontal cortex D1 receptors cause negative and cognitive symptoms (Lau et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The dopamine theory of schizophrenia, based on hyperactive dopamine projections in the mesolimbic system and reduced dopamine projections in the mesocortical system (Juárez Olguín et al, 2016), is the prevalent explanation of schizophrenia symptoms now. Alterations in striatal D2 receptors cause positive symptoms, and impairments in the prefrontal cortex D1 receptors cause negative and cognitive symptoms (Lau et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since dopamine is positively charged, this species is effectively repelled by the positively charged ionene, and very high concentrations are needed in order to be detected at the modified electrode (see Figure S7b). We point out that in physiological fluids the concentration of dopamine is much lower (on the order of 0.5-4.8 nM) [68] than that of ascorbic acid, hence the situation represented here is unrealistic. The analysis of the DPVs performed at 1% HMT-PMBI suggests that chronoamperometry could be useful for the quantification of both AA and UA, but with the requirement of performing the experiment at different applied potentials to avoid interferences.…”
Section: Detection Of Uric and Ascorbic Acids In Hmt-pmbi-coated Elecmentioning
confidence: 82%
“…Record of brain activity using Electroencephalography (EEG) indicated that after a subject played casual video game (Solitaire for Windows XP), there was a balance between right/left alpha power of the brain which entails mood stability and relaxation. The increase of extracellular dopamine during gaming activity may activate reward system in the brain which gives rise to happiness in game players (Juárez et al, 2016;Koepp et al, 1998). In addition, dopamine also has positive effect on learning process, motivation, and memory formation in hippocampus (Shohamy & Adcock, 2010).…”
Section: Resultsmentioning
confidence: 99%